Frontier marshal [videorecording (DVD)] - Scott, Randolph, 1898-1987; Kelly, Nancy, 1921-1995; Romero, Cesar, 1907-1994; Barnes, Binnie, 1903-1998; Carradine, John; Lake, Stuart N.; Hellman, Sam; Kaylin, Samuel, 1892-1983; Dwan, Allan, 1885-1981 (20th Century Fox cinema archives., 2012)
The prequel to My Darling Clementine, starring Randolph Scott as Wyatt Earp.